Perlindungan Hukum terhadap Tenaga Medis di Faskes Pertama dalam Pelayanan Kesehatan di Wilayah Puskesmas Sinar Rejeki Lampung Selatan - Oktavery Parasian Siahaan Siahaan; M. Fakih; HS Tisnanta (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The issue of legal protection for medical personnel in primary health care facilities remains a crucial concern in Indonesia’s health law enforcement. This study aims to analyze the forms of legal protection for medical personnel at Puskesmas Sinar Rejeki, Lampung Selatan, particularly in relation to professional negligence and the resulting legal implications from both criminal and civil law perspectives. The research applies a normative juridical approach by reviewing statutory regulations, legal doctrines, and relevant scholarly literature. The findings indicate that the protection of medical personnel is explicitly regulated under Law No. 17 of 2023 on Health and Government Regulation No. 28 of 2024, which guarantee occupational safety, legal certainty, and professional rights. Preventive protection includes licensing requirements and professional standards, while repressive protection involves mechanisms for resolving medical disputes through recommendations from the Indonesian Medical Disciplinary Board (MKDKI) prior to litigation. The study concludes that strengthening institutional supervision and legal literacy among medical practitioners is essential to ensure effective legal protection and uphold patient safety within primary health care services.